1994
DOI: 10.1073/pnas.91.9.3872
|View full text |Cite
|
Sign up to set email alerts
|

CD4 is a critical component of the receptor for human herpesvirus 7: interference with human immunodeficiency virus.

Abstract: In this study, we demonstrate that the glycoprotein CD4, a member of the immunoglobulin superfamily, is a critical component of the receptor for human herpesvirus 7 (IIHV-7), a recently discovered T-lymphotropic human herpesvirus. A selective and progressive downregulation of the surface membrane expression of CD4 was observed in human CD4+ T cells in the course of HHV-7 infection. Various murine monoclonal antibodies to CD4 and the recombinant soluble form of human CD4 caused a dose-dependent inhibition of HH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
130
1
7

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(148 citation statements)
references
References 18 publications
(15 reference statements)
7
130
1
7
Order By: Relevance
“…3 and 27, see ref. 29) and indeed the CD4 molecule appears to be a component of the viral receptor (30,31). Attempts to infect terminally differentiated macrophages have not been successful (32).…”
mentioning
confidence: 99%
“…3 and 27, see ref. 29) and indeed the CD4 molecule appears to be a component of the viral receptor (30,31). Attempts to infect terminally differentiated macrophages have not been successful (32).…”
mentioning
confidence: 99%
“…HHV-7 is a T-lymphotropic virus, using CD4 as a cellular receptor [Yasukawa et al, 1997], that replicate in CD4 þ T cells and the SupT1 cell line in vitro [Lusso et al, 1994]. Kempf et al [1997] reported that HHV-7 antigens were detected in CD68þ monocyte/macrophage lineage cells in tissues from patients with Kaposi's sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The present work and the recent study by Lusso et al (1994) have shown that HHV-7 and HIV-1 compete for cell surface CD4 as their binding receptor. Identification of the HHV-7 structure that binds to the CD4 molecule might allow the development of a subcomponent peptide derived from HHV-7 that selectively inhibits HIV binding but does not affect CD4 + T cell functions.…”
mentioning
confidence: 81%
“…Lusso et al (1994) and our group (Furukawa et al, 1994) have recently found that HHV-7 infection results in a marked decline in surface CD4 expression and functional alteration of CD4 + T cells. It is well known that such down-modulation of expression of surface CD4, which is the receptor for human immunodeficiency virus-1 (HIV-1), also occurs in HIV-l-infected cells (Hoxie et al, 1986a;Stevenson et al, 1987;Salmon et al, 1988;Kawamura et al, 1989;Geleziunas et aI., 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation